2014
DOI: 10.1016/j.surg.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations and patient-reported outcomes in surgery: A systematic review

Abstract: Background Recent events in healthcare reform have brought national attention to integrating patient experiences and expectations into quality metrics. Few studies have comprehensively evaluated the effect of patient expectations on patient-reported outcomes (PROs) following surgery. The purpose of this study is to systematically review the available literature describing the relationship between patient expectations and postoperative PROs. Methods We performed a search of the literature published prior to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
155
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 96 publications
5
155
0
7
Order By: Relevance
“…However, evidence concerning the importance of fulfilment of preoperative expectations is inconclusive [38]. The present study shows that unfulfilled expectations can be one reason for a negative view of the intervention outcome, and this is in line with previous research findings arguing for the importance of fulfilment of expectations [30,39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, evidence concerning the importance of fulfilment of preoperative expectations is inconclusive [38]. The present study shows that unfulfilled expectations can be one reason for a negative view of the intervention outcome, and this is in line with previous research findings arguing for the importance of fulfilment of expectations [30,39].…”
Section: Discussionsupporting
confidence: 90%
“…Expectations are multifaceted [40] and may evolve and change [34], and can therefore be difficult to measure [38]. In the present study, expectations of the trajectory of illness changed over time.…”
Section: Discussionmentioning
confidence: 76%
“…Yet in surgery inconsistency is common, and a sedulous sense of urgency must be established to stay ahead of the curve in the rapidly evolving delivery of health care in North America and the world. 4 In this month's issue, Wood et al, 5 in their paper entitled ''Surgical Management of Bone Metastases: Quality of Evidence and Systematic Review,'' attempt to address the question of just how well we are doing to help our MBD patients by employing a very stringent literature review. While patients afflicted with MBD may have limited life expectancies, we must still strive to optimize patient satisfaction and reported outcomes.…”
mentioning
confidence: 99%
“…Patient-reported outcomes (PROs) have become increasingly popular in assessing post-surgical interventions, especially post-spine surgeries, and are becoming the new standard for measuring many clinical outcomes (1,2). Multiple factors are incorporated in the PROs collected and assessed for post-surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors are incorporated in the PROs collected and assessed for post-surgical interventions. In a systematic review of 13,806 post-surgical patients, Waljee and colleagues found of the PROs available 64% of the patients were assessed for disability and 25% for pain, with only 5% assessed for mood disorders (2).…”
Section: Introductionmentioning
confidence: 99%